Problemática y propuesta de mejoramiento ambiental en la ciudad de laredo. la libertad - Perú - López Vásquez, Jorge Juan (2013)
The research analyzes and reports on urban environmental situation Laredo, assessing the effects of anthropogenic activities on the environment, warning about environmental threats, and how human activities affect the urban environment. The objective was to determine the effects of economic activities on the environmental quality of the city of Laredo, making the current diagnosis of jurisdiction, and to evaluate and assess the use and pollution activities of the urban area, establishing human activity relationship, environmental quality, and environmental improvement by proposing to manage the state of the city. The sample consisted of anthropogenic activities that pose risks to health and the environment as industrial activity, irregular settlements, market trade, urban construction, raising pigs, leather, liquid effluent discharge, nightclubs, available waste, fleet, bakeries, poultry, solid waste burning, restaurants, health service, carpentry shops, welding shops, fuel sales and sale of briquettes. It was found that the city Laredo presents sprawl in urban development, unplanned, no landfill solid waste treatment, sewage and industrial city is discharged into crop fields of Laredo SAA Sugar Industry bring bread and land without oxidation pond treatment, marketing and storage of fuel taps represents danger to human health, risk of spills, fires and explosion by burning sugarcane. The market does not meet proper operating requirements; economic activities by not properly administered cause pollution to human health risk. The city has poor air quality due to past and current municipal authority.